Staff Training and the Use of Artificial Intelligence (AI) in University Libraries - Abiolu, Oluremi Adenike; Akinyemi, Omolabake Eunice (International Journal of Knowledge Content Development & Technology, 2025)
AI has emerged as a transformative force in university libraries, enhancing service delivery and research skills. However, the successful use of AI for library operations depends profoundly on the readiness and training of the library staff. This study explores staff training and the use of AI in university libraries. A survey design was employed for the study. The study population was 91, comprising all the librarians (professional librarians) working in nine selected university libraries in Ondo, Osun, and Ekiti States, Southwest Nigeria. A census sampling method was used for the study. An online Google Form questionnaire was used to elicit data from the participants. Descriptive statistical tools and Pearson Product Moment Correlation Analysis were used for data analysis. The findings revealed that AI training, such as introductory training on AI fundamentals, Programming and Coding, evaluation of AI, Conferences and Workshops on AI, and ethical considerations of AI, among others, are required for artificial intelligence in university libraries. The study also found a significant relationship between staff training and AI use in university libraries in Southwest, Nigeria. Recommendations were made based on the findings that the university library management should organise regular on-the-job training for staff, focusing on the use of ICT. Also, library management should collaborate with AI experts or AI training institutes to offer specialised training programs tailored to the use of AI in libraries.